Author Correction: Coral carbon isotope sensitivity to growth rate and water depth with paleo-sea level implications - Braddock K. Linsley (Nature Portfolio, 2019)
The original version of the Source Data associated with this Article included an error, in which the ‘Fiji AB d13C-Suess’ data point and the ‘TNI2 d13C-Suess Effect’ data point for the year ‘1950.5’ where incorrectly omitted from the Figure 3 tab. The missing values are ‘−0.24’ and ‘−0.64’, respectively. The HTML has been updated to include a corrected version of Source Data.